1997
DOI: 10.1002/(sici)1098-1136(199710)21:2<204::aid-glia4>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Deprenyl induces GFAP immunoreactivity in the intact and injured dopaminergic nigrostriatal system but fails to counteract axotomy-induced degenerative changes

Abstract: There is increasing evidence of a trophic‐like mechanism for some effects ascribed to deprenyl therapy in the central nervous system. For that, we studied the effect of chronic treatment with deprenyl in an animal model of Parkinson's disease induced by unilateral knife transection of the medial forebrain bundle (MFB) in adult rats. The experimental conditions included a 3‐week pretreatment with deprenyl before stereotaxic transection of the MFB. Following surgery, deprenyl treatment was maintained for 3 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In this regard, whereas several MAO‐B inhibitors (including l ‐deprenyl) are reported to diminish GFAP expression in C6 glioma cells (Li et al, 1993), other authors support the idea that the MAO‐B inhibitor l ‐deprenyl increases GFAP immunoreactivity after injury in the rat brain (Biagini et al, 1993). Additionally, other reports suggest that, regardless of this l ‐deprenyl‐induced increase in GFAP immunoreactivity, l ‐deprenyl failed to counteract axotomy‐induced nigrostriatal degeneration (Revuelta et al, 1997). These data suggest that understanding the role of MAO‐B inhibitors in regulating astrocytic reactivity requires further study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In this regard, whereas several MAO‐B inhibitors (including l ‐deprenyl) are reported to diminish GFAP expression in C6 glioma cells (Li et al, 1993), other authors support the idea that the MAO‐B inhibitor l ‐deprenyl increases GFAP immunoreactivity after injury in the rat brain (Biagini et al, 1993). Additionally, other reports suggest that, regardless of this l ‐deprenyl‐induced increase in GFAP immunoreactivity, l ‐deprenyl failed to counteract axotomy‐induced nigrostriatal degeneration (Revuelta et al, 1997). These data suggest that understanding the role of MAO‐B inhibitors in regulating astrocytic reactivity requires further study.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, it has also been suggested that MAO‐B inhibitors may directly regulate astrocyte reactivity, although results seem to be controversial. Although some authors report that deprenyl increases the density of reactive astrocytes as assessed by glial fibrillary acidic protein (GFAP) immunoreactivity (Biagini et al, 1993; Revuelta et al, 1997), others suggest that deprenyl and other MAO‐B inhibitors decrease GFAP expression (Li et al, 1993). Hence, the potential usefulness of MAO‐B inhibitors in regulating astrocytic response must be clarified.…”
mentioning
confidence: 99%
“…However, some of the in vivo results suggest that selegiline protects and rescues A9 nigral neurons against oxidative stress and degeneration caused by MPP ϩ via mechanisms independent of its capacity to inhibit MAO-B enzymatic activity. Prior studies also indicated that selegiline may induce antioxidative and neurotrophic genes for enhancing neuronal survival in vivo (Carrillo et al, 1991;Vizuete et al, 1993;Kitani et al, 1994;Semkova et al, 1996;Tatton et al, 1996;Revuelta et al, 1997;Kunikowska et al, 2002). Nevertheless, it should be noted that selegiline rescues only moderately affected midbrain dopamine neurons in vivo (Wu et al, 1995).…”
Section: Selegiline Induces Trx Expression That Prevents Mppmentioning
confidence: 99%
“…It also prevents the ironcatalyzed auto-oxidation of dopamine to melanin. Furthermore, selegiline protection of brain neurons could be augmented by its unique capacity to induce Cu/ZnSOD, MnSOD, catalase, Bcl-2, GDNF, and NGF (Carrillo et al, 1991;Vizuete et al, 1993;Kitani et al, 1994;Semkova et al, 1996;Tatton et al, 1996;Revuelta et al, 1997;Kunikowska et al, 2002). Selegiline may also bind to glyceraldehyde-3-phosphate dehydrogenase, which is known to be associated with apoptotic cell death (Tatton et al, 2003).…”
mentioning
confidence: 99%
“…Ballabriga et al, 1997;Revuelta et al, 1997;Rothblat and Schneider, 1998;Thiffault et al, 1997;Vaglini et al, 1996). Ballabriga et al, 1997;Revuelta et al, 1997;Rothblat and Schneider, 1998;Thiffault et al, 1997;Vaglini et al, 1996).…”
Section: Introductionmentioning
confidence: 99%